Student teachers’ social capitals and motivations on online help-seeking - Liu, Shih-Hsiung (Advances in Social Sciences Research Journal, 2016)
Requesting help online is a quick way to obtain information to solve practicum-related problems for student teachers because they often serve a poor mentoring quality. The success in acquiring useful information by online help-seeking depends on subjects who are sought and their relationships with seekers. This study investigated the frequency of online help-seeking from two types of social capitals for student teachers in need of suggestions for practicum-related problems and determined the relationships among the amount of social capitals for, perceived benefits of, and motivations on, online help-seeking. A total of 246 Taiwanese secondary student teachers were invited to complete a survey in December 2015. This study concluded that the student teachers sought helps from bonding social capital more than from bridging social capital (BrSC) when meeting practicum-related problems; however, when they have high frequency of help-seeking from BrSC, they could maintain higher amount of BrSC and perceived higher benefits of help-seeking than those with low frequency. Additionally, the perceived benefits of online help-seeking were associated to the motivations of online help-seeking. If student teachers perceive high benefits of online help-seeking, especially from BrSC, they would be willing to seek help online.